Motivational Factors Underlying the Intention of Herbal Soap Entrepreneurs to obtain Halal Certificate in Malaysia - Mazita, Mokhtar; Salme, Yahya; Zetty Ain, Kamaruzzaman; Muhammad Waris, Ali Khan (Universiti Sains Islam Malaysia (USIM), 2022)
The goal of this study is to determine the motivation factors underlying Herbal soap entrepreneurs‘ intention to obtain Halal certificate in Malaysia. This is a quantitative study that employs questionnaires as a research tool and uses Dimaggio and Powell's (1983) model on institutional theory to study the intention of Herbal soap entrepreneur in getting Halalcertificate. The study predicted that there are positive links between Malaysian Herbal soap entrepreneurs’ motivation factors (coercive isomorphism, normative isomorphism and mimetic isomorphism) and the intention to obtain a Halal certificate. This study will have significant implications for various Halal stakeholders. Furthermore, despite the fact that many studies have focused primarily on the Halal food sector, there is a need for more research into the Halal Herbal soap market. More empirical and non-empirical research is needed to reveal more concerns with Halal certification in the Herbal soap industry.